Cases in financial management in education - Diaz, Clodualdo C. 1928-
The International School campaign for support of its development program and the Colegio de Sta. Brigida's college phase out due to financial problems are presented with extensive data from institutional documents: case records, letters of school officials, minutes of the meetings of the school Board of Trustees, school organ, bulletin of information, school budget, Presidential Decree no. 732, and court orders. To verify, clarify, and augment some of the documentary data, the researcher interviewed school officials, faculty members, and knowledgeable school personnel. Drama and emotional undercurrents are revealed through the use of dialogues and narrative techniques.